Enantioselective metabolism of phenylpyrazole insecticides by rat liver microsomal CYP3A1, CYP2E1 and CYP2D2 - Zhang, Zhaoxian; Wang, Zhiqiang; Li, Qing X.; Hua, Rimao; Wu, Xiangwei (Pesticide biochemistry and physiology, 2021)
The stereoselective difference of chiral pesticide enantiomers is an important factor of risk evaluation and the subject has received wide attention. In the present work, enantioselective metabolism of chiral phenylpyrazole insecticides including fipronil, ethiprole and flufiprole in rat liver microsomes was investigated in vitro. The result showed remarkable enantioselectivity for fipronil and ethiprole with the EF values of 0.11–0.58. The metabolite fipronil-sulfone was formed with the degradation of fipronil. R-Ethiprole to S-ethiprole transformation was observed, but not S-ethiprole to R-ethiprole. No enantioselective metabolism was observed for flufiprole with the EF values of 0.49–0.51. The enzymatic assays showed that the inhibition ratio of R-fipronil and S-ethiprole was 1.5–2.1times that of the corresponding enantiomers on CYP2E1 and CYP2D2 activity, leading to the enantioselective metabolism. The result of the homology modeling and molecular docking further revealed that S-fipronil (−7.56 kcal mol−1) and R-ethiprole (−6.45 kcal mol−1) performed better binding with CYP2E1 and CYP2D2, respectively. The results provided useful data for the risk evaluation of chiral phenylpyrazole insecticides on ecological safety and human health. [Display omitted] •Fipronil and ethiprole is remarkable metabolic enantioselectivity.•The metabolite fipronil sulfone with higher toxic was formed in liver microsomes.•R-Ethiprole is transformed to S-ethiprole in rat liver microsomes.•CYP2E1 and CYP2D2 mediate the enantioselectivity of fipronil and ethiprole.